2018
DOI: 10.1007/s10608-018-9989-3
|View full text |Cite
|
Sign up to set email alerts
|

Drive for Thinness Versus Fear of Fat: Approach and Avoidance Motivation Regarding Thin and Non-thin Images in Women

Abstract: Internalization of sociocultural attitudes regarding the so-called virtues of thinness and vices of fatness can lead to two motivational orientations: drive for thinness and fear of fat. The current study assessed drive for thinness and fear of fat, via approach and avoidance motivation towards thin-ideal and non-thin bodies respectively, and also the relation between these approach-avoidance tendencies and key eating disorder-related constructs. Participants were 95 female undergraduate students. Results reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 53 publications
(82 reference statements)
4
46
1
Order By: Relevance
“…Interestingly, Leins et al (2018) also failed to replicate an approach bias toward thin pictures, illustrating how difficult it generally is to reliably capture approach-avoidance behavior toward body images. This might also be caused by their use of computer-generated bodily stimuli (avatars; e.g., Woud et al, 2011;Leins et al, 2018;Dondzilo et al, 2019). We tried to overcome this limitation by using self-pictures compared to other-pictures, however, this did not lead to a more differential pattern between groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, Leins et al (2018) also failed to replicate an approach bias toward thin pictures, illustrating how difficult it generally is to reliably capture approach-avoidance behavior toward body images. This might also be caused by their use of computer-generated bodily stimuli (avatars; e.g., Woud et al, 2011;Leins et al, 2018;Dondzilo et al, 2019). We tried to overcome this limitation by using self-pictures compared to other-pictures, however, this did not lead to a more differential pattern between groups.…”
Section: Discussionmentioning
confidence: 99%
“…The approach -avoidance tendencies were associated to general symptoms of ED (thin internalization, drive to thinness, body dissatisfaction, etc.). More recently, Dondzilo et al (2019) applied an AAT in undergraduate females with thin-ideal vs. non-thin pictures. Results confirmed hypothesized approach tendencies toward thin-ideal bodies and showed an avoidance bias for non-thin body pictures.…”
Section: Introductionmentioning
confidence: 99%
“…By definition, thin-ideal internalization equates thinness with what is ideal and implies that being overweight is perceived as a negative characteristic. It has been argued that the positive valence accorded to thinness can result in approach motivation toward thin bodies, whereas fatness can prompt avoidance of overweight bodies due to its negative valence (see Dondzilo et al, 2019 for a discussion). Approach and avoidance responses to different body types have been associated with greater levels of eating pathology in both clinical and analogue samples using self-report questionnaires (Mussap, 2007;Rodgers et al, 2018), behavioural tasks THIN-IDEAL INTERNALIZATION AND REACTIONS TO FOOD 4 (Dondzilo et al, 2019;Woud et al, 2011), and measures of physiological response (Clarke et al, 2016;Dodd et al, 2017).…”
Section: Thin-ideal Internalization and Reactions To Foodmentioning
confidence: 99%
“…Thin-ideal internalization has been found to play a role in the relationship between approach and avoidance motivation and eating pathology. Several studies have demonstrated that greater thin-ideal internalization is associated with both a stronger approach response toward thin bodies (Dondzilo et al, 2019) and an increased avoidant response to overweight bodies (Woud et al, 2011). Furthermore, Mussap (2007) found that relationships between both sensitivity to reward and punishment (indicative of general approach and avoidance motivation) and eating pathology were mediated by thin-ideal internalization.…”
Section: Thin-ideal Internalization and Reactions To Foodmentioning
confidence: 99%
“…Researchers then began to use image and video distortion techniques that involved adjusting body image widths to produce a body size change (Slade, 1985; Taylor and Cooper, 1992; Skrzypek et al, 2001). However, it has now been established that horizontal stretching not only gives the body an unrealistic appearance, but can also preserve key size markers in the original image, such as hip-to-waist ratios, which may impact the validity of findings (Dondzilo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%